Topography of selectively laser melted surfaces: A comparison of different measurement methods. Issue 1 (2017) - Thompson, Adam; Senin, Nicola; Giusca, Claudiu; Leach, Richard
Abstract: Selective laser melting (SLM) of metals produces surface topographies that are challenging to measure. Multiple areal surface topography measurement technologies are available, which allow reconstruction of information rich, three-dimensional digital surface models. However, the capability of such technologies to capture intricate topographic details of SLM parts has not yet been investigated. This work explores the topography of a SLM Ti6Al4V part, as reconstructed from measurements by various optical and non-optical technologies. Discrepancies in the reconstruction of local topographic features are investigated through alignment and quantitative assessment of local differences. ISO 25178-2 areal texture parameters are computed as further comparison indicators.